Net Neutrality: A Fast Lane to Understanding the Trade-offs - Valletti,T; Peitz,M; Greenstein,S (Journal of Economic Perspectives, 2016)
The “net neutrality” principle has triggered a heated debate and advocates have proposed policy interventions.In this paper, we provide perspective by framing issues in terms of the positive economic factors at work. We stress the incentives of market participants, and highlight the economic conflicts behind the arguments put forward by the different parties. We also identify several key open questions.